PRICE BEHAVIOR AROUND EARNINGS ANNOUNCEMENT OF NEWLY LISTED SHARES - Mansor Md. Isa; Rubi Ahmad; Chan Yik Wan (Asian Academy of Management Journal, 1996)
Oversubcription for new equity issues has become a common phenomena in the Malaysian capital market. The strong public support to these new equity issues is mainly due to the high expected return predicted by the investors. Studies conducted on Malaysian capital market and those in other countries have shown that investors would most likely make excess returns on their investments not just on the initial listing but also thereafter. In the local scene. Ku Ismail, Abidin and Zainuddin (1993) finds that excess returns ranged from 19.74% (for hotel) to 125% (for industrial and commercial).